Visualizing and analyzing dynamic meteorological data with virtual globes: A case study of tropical cyclones. (February 2015) - Liu, Po; Gong, Jianhua; Yu, Miao
Abstract: Visualization is an important component of the evaluation of meteorological models, forecasting research, and other applications. With advances in computing power, the volume of meteorological data generated by geoscience and climate researchers has been steadily increasing. The emerging technique of virtual globes has been regarded as an ideal platform for visualizing larger geospatial data over the Internet. To visualize and analyze meteorological data with the new virtual globes, this paper proposes a systematic meteorological data visualization (MDV) framework in World Wind, an open-source virtual globe. The key technologies, including a hierarchical octree-based multiresolution data organization, data scheduling, level of detail (LOD) and rendering are described in detail. The framework is then applied to a practical tropical cyclone simulation, including flow vectors, particle tracking, cross-sectional analysis, streamlines, pathway animation, and volume rendering. The results show that virtual globes are effective tools for meteorological data visualization and analysis. Graphical abstract: Highlights: We propose a systematic visualization framework for meteorological data. A hierarchical octree-based multi-resolution data structure is implemented. The 3D-texture mapping algorithm is improved on the GPU. A virtual globe application for tropical cyclones is presented.